PDE4 and Epac1 Synergistically Promote Rectal Carcinoma via the cAMP Pathway - Xiangyu Kong; Ganghao Ai; Dai Wang; Renzhen Chen; Dongbei Guo; Youliang Yao; Kai Wang; Guiye Liang; Fengjie Qi; Wenzhi Liu; Yongxing Zhang (Analytical Cellular Pathology)
Objective. To assess the expression levels of exchange protein 1 directly activated by cAMP (Epac1) and phosphodiesterase 4 (PDE4) in rectal carcinoma, and their associations with clinicopathological indexes. In addition, the associations of PDE4 and Epac1 with A-kinase anchor protein 95, connexin 43, cyclin D1, and cyclin E1 were evaluated. Methods. The PV-9000 two-step immunohistochemistry method was used to determine protein expression in 44 rectal carcinoma tissue samples and 16 paracarcinoma tissue specimens. Results. The positive rate of PDE4 protein expression in rectal carcinoma tissues was higher than that of paracarcinoma tissues (59.09% vs. 12.5%, P<0.05). Similar findings were obtained for Epac1 (55% vs. 6.25%, P<0.05). No significant associations of PDE4 and Epac1 with degree of differentiation, histological type, and lymph node metastasis were found in rectal carcinoma (P>0.05). Correlations between PDE4 and Epac1, PDE4 and Cx43, PDE4 and cyclin E1, and Epac1 and Cx43 were observed (all P<0.05). There was no correlation between the other protein pairs examined (P>0.05). Conclusion. PDE4 and Epac1 expression levels are increased in rectal carcinoma tissues, suggesting that the two proteins may be involved in the development of this malignancy. Meanwhile, correlations between PDE4 and Epac1, PDE4 and Cx43, PDE4 and cyclin E1, and Epac1 and Cx43 suggested synergistic effects of these proteins in promoting rectal carcinoma.